2013
DOI: 10.1111/tri.12068
|View full text |Cite
|
Sign up to set email alerts
|

In situ lung perfusion is a valuable tool to assess lungs from donation after circulatory death donors category I-II

Abstract: SummaryDonations after circulatory death (DCD) lung grafts are an alternative to extend the donor pool in lung transplantation. This study investigates the use of an in situ lung perfusion system (ISLP) in the donor to evaluate category I-II lungs. Pigs were sacrificed by ventricular fibrillation. All animals underwent 20 min of cardiopulmonary resuscitation and 5 min hands-off period after which heparin was administered. In group [WI-1], this was followed by 1 h of warm ischemia (WI) and 2 h of topical coolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…We found that a decrease in compliance and high or increased airway pressure after 2 h of EVLP were the decisive parameters when rejecting lungs, even when they initially met the acceptance criteria for transplantation. This was also demonstrated in our previous animal study of in situ lung perfusion, in which compliance and plateau airway pressures were better in less badly injured donor lungs ( 18 ). Two lungs with a pO 2 above 60 kPa were declined for transplantation due to a decrease in compliance, an increase in plateau airway pressure and pulmonary vascular resistance, and an obvious pulmonary edema upon inspection.…”
Section: Discussionsupporting
confidence: 75%
“…We found that a decrease in compliance and high or increased airway pressure after 2 h of EVLP were the decisive parameters when rejecting lungs, even when they initially met the acceptance criteria for transplantation. This was also demonstrated in our previous animal study of in situ lung perfusion, in which compliance and plateau airway pressures were better in less badly injured donor lungs ( 18 ). Two lungs with a pO 2 above 60 kPa were declined for transplantation due to a decrease in compliance, an increase in plateau airway pressure and pulmonary vascular resistance, and an obvious pulmonary edema upon inspection.…”
Section: Discussionsupporting
confidence: 75%
“…It has an internal roller pump to create a continuous flow. The Lung Assist ® is a less robust device with individual components mounted on a frame designed for EVLP and for in situ evaluation of lungs from uncontrolled DCD at the donor site prior to explanting the organs from the body . Finally, the XPS ™ is a fully integrated device that was developed based on the principles of the Toronto technique.…”
Section: Evlp Technology and Devicesmentioning
confidence: 99%
“…Lung Assist® (Organ Assist, Groningen, the Netherlands) is deemed "a less robust device with its individual components fixed on a frame designed for EVLP, and for in situ evaluation of lungs from uncontrolled DCD at the donor site, prior to explanting the organs from the body" [14,35].…”
mentioning
confidence: 99%